Empowering mothers of children under two to prevent stunting through a healthy kitchen - Lisda Widianti Longgupa; Fransisca Noya; Sony Bernike Magdalena Sitorus; Febty Kuswanti (Universitas Muhammadiyah Magelang, 2024)
Stunting is a national health issue with significant implications for the quality of future generations, making it a priority for the government at both central and local levels. This community service program aimed to enhance the knowledge and skills of mothers with children under two years old (infants) and posyandu cadres in Lembomawo Village, Poso Kota Selatan Subdistrict, on utilizing local food ingredients for supplementary feeding (PMT). Through counseling and cooking demonstrations, participants were introduced to three PMT recipes tailored to the food texture requirements of infants: 6–8 months (Bubur Singkong Kukuruyuk Saus Jeruk), 9–11 months (Nasi Tim Ikan Telur Sayuran), and 12–23 months (Tim Ikan Menado). Additionally, recipe books for local infant and maternal nutrition were distributed to mothers and posyandu cadres to serve as practical guidelines. The results of the program showed a significant increase in mothers' knowledge about the importance of supplementary feeding using local ingredients, from 23.6% prior to the intervention to 85.72% afterward. This program was conducted in collaboration with the Village Midwife and the Lembomawo Village Government, aiming to contribute to reducing stunting rates through sustainable utilization of local resources.